Resilient Water Supply and Sanitation Services : The Case of Japan - World Bank (World Bank, Washington, DC, 2018)
Natural disasters have increasingly damaged water supply and sanitation (WSS) facilities and infrastructure, leaving entire communities without safe and reliable drinking water and the appropriate disposal of wastewater. These emergency events could arise from inundation of facilities, loss of electricity, and exposure and disruption of infrastructures. Less severe impacts can arise from increased siltation of reservoirs and slow-onset events such as droughts, thus having longer-term effects on the resilience and reliability of services. These WSS service failures or interruptions could set off a cascading effect across interconnected infrastructure systems including public health and fire services, which in turn could pose both direct and indirect economic impacts. Japan has built the resilience of its WSS services through an adaptive management approach based on lessons learned from past natural disasters. This experience offers key insights for low- and middle-income countries seeking to sustain and build resilience of WSS services.